GROWTH AND YEILDS OF Indigofera zollingeriana PLANTS FERTILIZED WITH LIMOUSINE COW MANURE AT DIFFERENT DOSAGE - E. S. D., Jesus; Witariadi, N. M.; Wirawan, I W. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the growth and yield of Indigofera zollingeriana plants fertilized with limousin cow manure at different dosage. This research was carried out in the Sesetan Laboratory Greenhouse, Faculty of Animal Husbandry, Udayana University, starting from February to April 2021. The experimental design used in this study was a completely randomized design (CRD) with five treatments and six replications. The five treatments were dosage of 0 tons ha -1 (D0), 10 tons ha -1 (D10), 20 tons ha -1 (D20), 30 tons ha -1 (D30), and 40 tons ha -1 (D40). The variables observed in the study were growth variables, production variables, and growth characteristics variables. The results showed that the application of limousin cow manure fertilizer could increase the total dry weight variable for Indigofera zollingeriana plants but did not have an effect on other variables. The conclusion of this study was that the yeilds of Indigofera zollingeriana was increased by giving dosage of limousin cow manure fertilizer. The application of limousine cow manure fertilizer at the level of 20 tons ha -1 gave the best results.   Key words: Growth, Indigofera zollingeriana, limousin cow manure fertilizer, yield